Albinism in the largest extant amphibian: A metabolic, endocrine, or immune problem? - Chang, Liming; Zhu, Wei; Jiang, Jianping (Frontiers in Endocrinology, 2022)
Background Pigment regression is an intriguing phenomenon that can be caused by disorders in melanin metabolism or endocrine regulation, or by autoimmune disorders. Albino animals serve as excellent models for the study of the genetic determination of morphology, particularly the evolution of and molecular mechanisms underlying chromatophore-related diseases in animals and humans. Material and Methods The artificial culture of Andrias davidianus, the largest extant amphibian, is flourishing in China due to the great ecological and economic value of this animal. Approximately 0.1% of individuals express an albino phenotype accompanied by delayed somatic growth and mortality at early developmental stages. In this study, brain and skin transcriptomics were conducted to study the underlying molecular basis of the phenotype. Results The results indicated decreased transcription of genes of melanin synthesis. Interestingly, MHC I isotypes and immune-related pathways accounted for the primary transcriptional differences between groups, suggesting that the albino phenotype represents a systematic immune problem to a far greater extent than a pigmentation defect. Albino individuals exhibited shifted transcription of MHC I isotypes, and the albino-specific isotype was characterized by increased charges and decreased space in the antigen- binding pocket, implying a drastic change in antigen specificity and a potential risk of autoimmune disorders. Conclusion These results suggest an association between the albino phenotype and MHC I variants in A. davidianus, which could serve as a convenient model for vitiligo or other autoimmune diseases.